Kendala-Kendala yang dihadapi Guru PAI dalam Menerapkan Self-Assessment di Madrasah Allyah Negri 4 Bone - R. Nurhayati; Sudirman P; Sartina; Suwito, Agus; Andra Ningsih, Diarti; Janna, Hasratul; Rahmat, Fajar (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
The purpose of this research is to describe how teachers at Madrasah Aliyah Negeri 4 Bone apply self-assessment to their students and the obstacles they face. There were 2 (two) PAI teachers at Madrasah Aliyah Negeri 4 Bone used as research subjects in this research. Qualitative techniques with a descriptive research approach were used in this research. Observations and interviews were used as data collection techniques. Inductive reasoning is used to assess data, from the specific to the general one. The findings of this research are that teachers at Madrasah Aliyah Negeri 4 Bone provide self-assessment to students during the learning process by observing and also using the curriculum assessment rubric and focusing on the learning process taking place and also outside the classroom. Obstacles faced by teachers in evaluating students at Madrasah Aliyah Negeri 4 Bone for good learning are a lack of time, a large number of students in one class up to 28 students, and difficulties in guiding students to behave well in accordance with learning objectives that can be achieved. In addition, many students do not complete an honest self-assessment.